3D tree-shaped hierarchical flax fabric for highly efficient solar steam generation. Issue 4 (6th January 2021) - Li, Yaping; Fan, Jie; Wang, Run; Shou, Wan; Wang, Liang; Liu, Yong
Abstract : A 3D hierarchical tree-shaped biomimetic flax fabric is fabricated and modified by one-step synthesis of polydopamine–polypyrrole composite nanofibers to achieve highly efficient solar steam generation, with great potential in water purification and seawater desalination. Abstract : Solar steam generation as a promising technology has great potential for application in wastewater treatment and seawater desalination. However, it remains challenging to develop low-cost, high-efficiency steam generators that are suitable for large scale application. Here, inspired by the natural transpiration process of trees, we fabricated a three-dimensional (3D) hierarchical tree-shaped biomimetic flax fabric (TBFF) using an ordinary loom, consisting of a float layer, basket weave layer and plain weave layer, which showed directional water transport properties along the continuous warp yarns of the fabric. Then, the obtained TBFF was modified by one-step synthesis of large-area polydopamine–polypyrrole composite (PDA–PPy) nanofibers for a high hydrophilicity and a higher surface area. The hierarchical micro-capillary pores of yarns and macro-interlaced pore structures between the warp and weft yarns in such modified TBFF-PDA-PPy exhibit broadband light absorption, high-efficiency water supply, large evaporation area, and easy steam escape. Therefore, the continuous water transport paths formed by TBFF-PDA-PPy could deliver an attractive evaporation rate of 1.37 kg m −2 h −1, where the solar energy conversion efficiency was up to 87.4% under 1 sun illumination. Based on the facile fabrication, low cost and scalable manufacturing process, this nature-inspired design of 3D hierarchical TBFF-PDA-PPy is expected to promote large-scale applications in water purification and seawater desalination.